Mechanical Response of Soft Rock Roadways in Deep Coal Mines Under Tectonic Stress and Surrounding Rock Control Measures - Anying Yuan; Chaofan Xu; Xin Tian (Applied Sciences, 2025)
This study focuses on how rocks respond mechanically and how to keep them stable when soft rock roadways are under deep tectonic stress. It does this through a combination of theoretical analysis, numerical simulations, and field applications. We created a mechanical model of roof strata to calculate how much they would bend under both horizontal tectonic stress and their weight. This modeling helped us determine the critical yield limits. A systematic study of the angle θ between the direction of tectonic stress and the axis of the roadway showed that the concentration of horizontal stress on the roof gets stronger as θ increases, while the vertical stress on the sidewalls slowly gets weaker. The main sign of surrounding rock failure is shear damage that is most severe at the roof, floor, and shoulder angles. The maximum plastic zone depth occurs at θ = 90°. Studies that looked at both gob-side and along-roadway stages found that the two types of failure were very different, characterized by severe roof damage during roadway advancement and pronounced coal pillar instability in gob-side conditions. Based on these results, targeted support strategies were successfully used in field engineering to control deformations and provide both theoretical foundations and practical solutions for stabilizing deep soft rock roadways under tectonic stress.